Nutritional status of Indigofera zollingeriana forage at different level draught stress and cutting interval - Herdiawan, Iwan; Abdullah, Luki; Sopandi, D (Indonesian Journal of Animal and Veterinary Sciences, 2014)
The low rainfall and high temperature greatly affect the decline in production and quality of forage in general. The experiment was arranged in a completely randomized design with two factors and four replications. The first factor consisted of 3 level of drought stress namely: 100% field capacity (FC) (control), 50% FC, and 25% FC. The second factor comprised of 3 defoliation interval i.e. interval defoliations of 60, 90 and 120 days. The observed variables were nutrient content (crude protein (CP), crude fibre (CF), Gross energy, lignin, selulose, neutral/acid detergent fibre (NDF/ADF), in vitro dry matter and organic matter digestibility (IVMD/IVOMD), Ash, Ca and P) and anti-nutrient content (Tannin and Saponin). Data were analyzed by ANOVA and the differences between treatments were tested by LSD. The results shows that there were interactions (P<0.05) between drought stress and defoliations interval on CP, CF, energy, cellulose, lignine, NDF/ADF, IVMD and IVOMD, but not to ash, Ca, P, saponin and tannin content. Drought treatment significantly (P<0.05) decreased CP, energy, IVMD and IVOMD, but CF, lignin, cellulose, ND/ADF, IVDMD/IVOMD, saponin and tannin increases. Defoliation interval significantly (P<0.05) decreases on CP, CF, energy, lignin, cellulose, NDF/ADF, and IVDMD/IVOMD, but saponin and tannin content did not affected. Key Words: I. zollingeriana, Drought Stress, Defoliation Interval, Nutrient, Anti-Nutrients